2022
DOI: 10.3390/atmos13060985
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of the WRF Model in a Hyper-Arid Environment: A Sensitivity Study

Abstract: Accurate simulation of boundary layer surface meteorological parameters is essential to achieve good forecasting of weather and atmospheric dispersion. This paper is devoted to a model sensitivity study over a coastal hyper-arid region in the western desert of the United Arab Emirates. This region hosts the Barakah Nuclear Power Plant (BNPP), making it vital to correctly simulate local weather conditions for emergency response in case of an accidental release. We conducted a series of high-resolution WRF model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
2
3
0
Order By: Relevance
“…The lower correlation observed in marine regions possibly arises from the more muted diurnal cycle (Fig.2) and the model's inability to properly represent the complex land-sea mask even at 3 km spatial resolution. Similar results were reported inAbida et al, (2022), where the WRF model demonstrates improved accuracy in inland areas compared to offshore or coastalregions. The RMSE (MAE) values stand at 3.57 °C (2.68 °C) for land and 1.67 °C (1.47 °C) for marine regions, respectively.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…The lower correlation observed in marine regions possibly arises from the more muted diurnal cycle (Fig.2) and the model's inability to properly represent the complex land-sea mask even at 3 km spatial resolution. Similar results were reported inAbida et al, (2022), where the WRF model demonstrates improved accuracy in inland areas compared to offshore or coastalregions. The RMSE (MAE) values stand at 3.57 °C (2.68 °C) for land and 1.67 °C (1.47 °C) for marine regions, respectively.…”
supporting
confidence: 87%
“…During the daytime, there is a tendency for the model to exhibit a warm bias, while at night and evening, a cold bias is more apparent. Such discrepancies in temperature have been reported before (Abida et al, 2022;Branch et al, 2021;Fonseca et al, 2021;Schwitalla et al, 2020;Temimi et al, 2020a). Overall, the WRF-Chem model displays a consistent cold bias of less than 0.5 °C for both environments during the summer months.…”
Section: Evaluation Against Surface-based Observationssupporting
confidence: 72%
See 2 more Smart Citations
“…This observation is expected, as the SHAMS location is further inland compared to other coastal locations, such as Barakah and Abu Dhabi. Previous studies conducted at Barakah reported the persistent occurrence of strong northwesterly winds for several days when the location is under the influence of favorable synoptic conditions (Abida et al, 2022;Nelli et al, 2022;Weston et al, 2022).…”
Section: Background Weather Conditions During Wise-uae Phase-1mentioning
confidence: 96%